The characteristics of Fe speciation and Fe-binding ligands in the Mariana back-arc hydrothermal plumes. (1st January 2021) - Wang, Hu; Resing, Joseph A.; Yan, Qiaoyang; Buck, Nathaniel J.; Michael, Susanna M.; Zhou, Haiyang; Liu, Meitong; Walker, Sharon L.; Yang, Qunhui; Ji, Fuwu
Highlights: We present the characteristics of Fe speciation and ligands in hydrothermal plumes over low- and high-temperature vents and over diffuse venting fields. Total Fe in plumes over the low-temperature hydrothermal vent contained the highest proportions of dissolved Fe and labile Fe. Diffuse flow had the highest proportion of dissolved Fe present as labile Fe. The linear relationships between Fe species and total Mn in the buoyant plume over Burke suggest a simple conservative mixing with ambient seawater. Organic Fe ligands in hydrothermal plumes constituted a significant portion of dissolved Fe and labile Fe. Abstract: We investigated the speciation of Fe and distributions of Fe-binding ligands in the hydrothermal plumes over high- and low-temperature vents and over diffuse venting fields above the Mariana back-arc spreading center. The concentrations of ligands ([L]) and conditional stability constants (K'FeL ) of the natural Fe ligand pool were measured by a reverse titration-competitive ligand exchange-adsorption cathodic stripping voltammetry (RT-CLE-ACSV). The results showed that the buoyant and non-buoyant plume samples over the low-temperature Burke had the highest dissolved Fe/total Fe (DFe/TFe) of 82.2 ± 8.8% and labile Fe/total Fe (FeLab /TFe) of 43.3 ± 5.6%. In contrast, in the plume samples above the high-temperature Perseverance field, TFe had the lowest proportions of DFe (48.8 ± 12.2%) and FeLab (19.4 ± 8.8%). The linear relationships between Fe species and total Mn (TMn) in the buoyant plume over Burke suggest a simple conservative mixing with ambient seawater, which resulted in constant values of DFe/TFe. However, in the non-buoyant plume over Burke, DFe/TFe decreased with plume dilution. The plume samples sourced from the diffuse flow over newly erupted lava had the highest proportion of DFe present as FeLab (74.6 ± 4.0%). The [L] in the buoyant plumes over low-temperature Burke vent were up to 113.6 nM, and the logK'FeL decreased with increasing DFe and [L], suggesting the importance of weaker ligands in stabilizing Fe. For all the plume samples, the organically complexed Fe (FeL) constituted significant proportions of the DFe (29.0 ± 9.3%) and FeLab (57.5 ± 15.6%) fractions. These Fe-binding ligands were likely sourced from diffuse venting fluids adjacent to the venting sites, and may be also produced by microbes within the hydrothermal plumes.